Developing Listening Skill Materials for First Semester Students in the Arabic Language Department, The New College, Chennai, India - K. M. A. Ahamed Zubair (Lingua : Journal of Linguistics and Language, 2025)
The listening materials previously used in the Arabic Language Department were primarily based on recordings centered exclusively on Arab culture, with no integration of the learners’ native Indian cultural context. This cultural gap made the materials difficult for students to relate to and comprehend, particularly in an environment where Arabic is rarely encountered outside the classroom. To address this issue, the study employed an explanatory sequential mixed-methods design. The qualitative phase, consisting of classroom observations and instructor interviews, was conducted to identify limitations in the existing materials and to guide the development of culturally responsive listening prototypes. The subsequent quantitative phase used a quasi-experimental pre-test and post-test control group design to evaluate the effectiveness of the developed materials. The sample consisted of 30 male first-semester undergraduate students divided into experimental (n=15) and control (n=15) intact classes. Data were collected using an observation checklist, a semi-structured interview guide, and a validated 30-item listening comprehension test. The operational hypothesis proposed that students exposed to culturally integrated materials would demonstrate greater improvement in listening comprehension than those using traditional materials. The results confirmed that the original materials relied solely on Arab-Islamic historical narratives unfamiliar to learners. Guided by feedback and relevance principles, the materials were revised to include familiar contexts such as religions in India, Indian heroes, and local social issues while retaining exercises. Statistical analysis showed a significant difference between experimental and control post-test scores. Therefore, the null hypothesis was rejected and the alternative hypothesis accepted, demonstrating that materials enhanced listening comprehension.